EKSPLORASI ETNOMATEMATIKA PADA BATIK SEKAR JAGAD BLAMBANGAN SEBAGAI BAHAN AJAR SISWA - Akmalia, Nabilah (Department of Mathematics Education , University of Jember, 2020)
Ethnomathematics is an activity carried out by a group of cultures where they are unaware that there is a basic application or concept of mathematics in it. Learning mathematics needs an approach that is able to connect mathematics with everyday culture. One of the cultures possessed by Indonesia is batik art. Batik Sekar Jagad Blambangan is a typical batik in Banyuwangi. This research aimss to describe the results of ethnomathematics exploration of Batik Sekar Jagad Blambangan and make student teaching materials student worksheet especially for grade XI Senior High School with geometry transformation material. This study used qualitative research with an ethnographic approach. The subjects are 2 craftsmen at Godho Batik house production in Banyuwangi. Data were collected by using observation, interview, and documentation. The result of this study indicates the existence of ethnomathematics at Batik Sekar Jagad Blambangan .There are some geometry concepts or elements found, such as: points, lines, angles, 2D shapes, congruence and geometric transformations.